The Hermeneutics of Postmodernity Figures and Themes - Madison, G. B. (Indiana University Press, 1988)
Does the end of modernism signal the onslaught of some form of anarchistic nihilism, as some today proclaim? Or can the traditional guiding notions of philosophy-in particular, meaning, truth, and reality-be revitalized in a nonfoundational, postmetaphysical, decidedly postmodern way? The figures about whom G. B. Madison writes are active participants in this unfolding debate: Husserl, Gadamer, Hirsch, Ricoeur, Merleau-Ponty, Derrida, Barthes, and Rorty. In a decidedly postmodern fashion, Madison also takes up such central themes as thenature of metaphysical thinking, metaphor, imagination, subjectivity, intersubjectivity, and the mind/body problem. Common to the essays presented here is a central preoccupation with the fate of philosophy and of traditional philosophical concerns in a postmodern age. Throughout, an attempt is made to bring into focus the decisive questions posed by the demise of foundationalist philosophy, of the epistemological subject and the objective world, and of the traditional, objectivistic ideas of knowledge and truth.